Analysis of Giant Reflectance Tuning Enabled by Unidirectional Guided Resonance With Embedded Absorber - Yuefeng Hu; Zixuan Zhang; Chenxingyu Huang; Qian Li; H. Y. Fu; Chao Peng (IEEE Photonics Journal)
Achieving giant reflectance tuning is essential for various applications, including optical communication, switching, processing, and sensing. While optical resonances effectively enhance light-matter interactions, their inherent dispersive nature limits the maximum achievable reflectance tunability at the resonant frequency. To overcome this challenge, we propose utilizing unidirectional guided resonances (UGRs) to deterministically close leaky channels, thereby concentrating energy flow in the desired direction. Through systematic analysis, we compare the reflectance response of UGRs with conventional guided resonances incorporating embedded absorbers, demonstrating that reflectance tunability can theoretically approach unity under ideal conditions. Furthermore, we introduce a realistic design incorporating electrically controlled indium tin oxide (ITO) with the epsilon-near-zero (ENZ) effect as an embedded absorber. Despite the absorbing layer being thinner than $1\,\text{nm}$ , the theory and simulation show that our design can support a reflectance tunability of 0.76 under a driving voltage of $3\,\text{V}$ . This approach presents a promising strategy for expanding the range of reflectance variations, enabling advancements in optical communication, computing, and beyond.